Identifikasi Jasa Ekosistem dan Valuasi Nilai Manfaat Langsung untuk Mendukung Pengelolaan Pariwisata Berkelanjutan (Studi Kasus di Kee Cukang Taneuh Desa Kertayasa Kabupaten Pangandaran) - Dita Agustian; Samuel Agus Triyanto; Diki Muhamad Chaidir (Universitas Riau, 2023)
The concept of sustainable development is a concept that links economic development, environmental quality, and social equity. These three aspects are the main pillars that must be considered in a balanced and proportional manner so that sustainable development can be optimally successful. This study used a descriptive qualitative approach with direct observation/observation techniques in the field as well as interviews with the managers of the Cukang Taneuh Essential Ecosystem Area (KEE) and local community leaders. Observations were made by exploring the areas included in the Cukang Taneuh KEE and directly recording the types of ecosystem services available. The data was obtained through an inventory of the types of ecosystem services contained in the Cukang Taneuh KEE accompanied by a description of the benefits of each of these ecosystem services. Data analysis on the value of direct benefits from ecosystem services in the area is carried out through the Total Economic Value (TEV) valuation approach. The results show that there are four types of ecosystem services in Cukang Taneuh KEE, namely provisioning services, regulatory services, cultural services, and supporting services. Then for the value of direct benefits for the value of direct benefits obtained from KEE Cukang Taneuh obtained from utilization as a tourist spot, utilization of fishery resources, and utilization of forest products with a total value of Rp. 11,787,625,000.00 per year.